The challenges in the formation of leader managers in health - Chanes, Marcelo (O Mundo da Saúde, 2006)
This study presents a historical retrieval on Leadership and presents its applicability in managers’ formation in the health field. It also presents the components considered the basis for the formation of leader managers in health like clear objectives, the recognition of motivational factors in the organizational vision, open and constant communication, decentralized power in the decision process, the establishment of relationship bonds, transformational leadership and innovation. From these elements, a parallel is traced between the current movement in the regulation regarding the formation of administrators, proposing some concerns to be thought about in the immediate future.